FUNGSI SATPOL PP DALAM PENEGAKAN PERDA NOMOR 7 TAHUN 2006 TENTANG KETERTIBAN UMUM DI KABUPATEN SAMBAS (Studi Kasus di Desa Jagur) - Tamrin, Marilang, Kurniati (Madani Legal Review, 2021)
Each district / city must have a plan to achieve in managing and regulating its government. One of them is in the aspect of order and peace. To carry out matters of peace, public order, and protection of the community, the local government formed Satpol PP. The focus of this research problem is how the function of Satpol PP in enforcing Regional Regulation Number 7 of 2006 concerning public order in Sambas Regency and what factors become obstacles. This study uses empirical legal research methods. The results of the study show that the function of the Satpol PP is based on the Sambas Regency Regional Regulation Number 4 of 2016 concerning the Formation and Organizational Structure of the Sambas Regency Regional Apparatus and the Sambas Regent Regulation Number 53 of 2016 concerning the Position, Organizational Structure, Duties, Functions and Work Procedures of the Pamong Praja Police Unit of Sambas Regency and factors inhibiting the implementation of the function, among others: the factor of the lack of personnel to enforce the regional regulation, the geographical factor of the very wide Sambas district, the factor of public awareness and the factor of facilities and infrastructure.